To Study the Role of Parental Encouragement on Self Concept and Adjustment of Adolescents: Exploring the Impact of Parental Encouragement on Adolescent Development (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Adolescence has been gotten from Latin word adolescere, signifying to grow up It is a transitional phase of physical and mental improvement that for the most part happens amid the period from adolescence to adulthood. It is a changeover age from youth to adulthood. It incorporates a youngster who has experienced adolescence yet who has not achieved full development.